Beyond the weaving ebook - Whyte, Campbell (Home Time., 2020)
Home Time: Under the River ended with a disastrous tea ceremony which left six kids lost, scared, confused, and even burnt. Now, the second half of the Home Time saga picks up from that nerve-wracking cliffhanger, as the children leave the relative safety of Peach Village in search of medicine, answers, and, hopefully, a way home. Equipped with a living map, a flask of hallucinogenic tea, and a plan so stupid it just might work, Lily, Amanda, Ben, and Nathan will have to pull together at the very time they've drifted the furthest apart. Award-winning graphic novelist Campbell Whyte is back, with his signature kaleidoscope of art styles, to cast a new spell wrapping up the most whimsically fantastical journey in ages. Author: Campbell Whyte. Illustrator: Campbell Whyte. Home Time © Campbell Whyte